Newest Update in Heart Failure Guidelines Recommendation - Hasanah Mumpuni (Faculty of Medicine, Public Health and Nursing Universitas Gadjah Mada, 2019)
Heart failure remains a global burden despite important progress that has been made in the management of heart failure. Guidelines from ESC and AHA are still widely used as a guidance for diagnosis and management of heart failure. We will discuss the new recommendation from ESC and AHA guideline for heart failure.